2017
DOI: 10.1002/adhm.201700980
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterials‐Based Approaches to Tumor Spheroid and Organoid Modeling

Abstract: Evolving understanding of structural and biological complexity of tumors has stimulated development of physiologically relevant tumor models for cancer research and drug discovery. A major motivation for developing new tumor models is to recreate the 3D environment of tumors and context-mediated functional regulation of cancer cells. Such models overcome many limitations of standard monolayer cancer cell cultures. Under defined culture conditions, cancer cells self-assemble into 3D constructs known as spheroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 200 publications
(421 reference statements)
0
100
0
Order By: Relevance
“…The natural proteins used as cell culture matrices are collagen, gelatin, fibrin, silk protein (mainly referring to silk fibroin), poly‐ l ‐lysine (PLL), and soy protein . These proteins can interact with cells and supply physiologically relevant microenvironments to guide cellular behaviors by presenting componential cues . In addition, Matrigel and decellularized extracellular matrices (dECM) are typical animal‐derived mixtures of various polysaccharides (e.g., HA and heparan), proteins (e.g., collagen and laminin), and growth factors.…”
Section: Snapshot Of Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural proteins used as cell culture matrices are collagen, gelatin, fibrin, silk protein (mainly referring to silk fibroin), poly‐ l ‐lysine (PLL), and soy protein . These proteins can interact with cells and supply physiologically relevant microenvironments to guide cellular behaviors by presenting componential cues . In addition, Matrigel and decellularized extracellular matrices (dECM) are typical animal‐derived mixtures of various polysaccharides (e.g., HA and heparan), proteins (e.g., collagen and laminin), and growth factors.…”
Section: Snapshot Of Hydrogelsmentioning
confidence: 99%
“…Synthetic hydrogels are often considered to be permissive biomaterials for cell culture due to their bioinert properties . The common synthetic polymers in previous reports include polyethylene glycol (PEG) and its derivates, polylactic acid (PLA), poly(lactic‐ co ‐glycolic acid) (PLGA), poly(vinyl alcohol) (PVA), poly(ε‐caprolactone) (PCL), polyacrylic acid (PAA), polyacrylamide (PAm), poly(2‐hydroxyethyl methacrylate) (PHEMA), and polyurethane (PU) . They are usually blended/modified with proteins (e.g., laminin) or peptides (e.g., Arg‐Gly‐Asp, RGD) to increase their biocompatibility for employment as 3D scaffolds.…”
Section: Snapshot Of Hydrogelsmentioning
confidence: 99%
“…In all matrices, E‐cadherin was enriched at cell–cell boundaries, and laminin‐332 appeared to be interspersed throughout the spheroid, with slight concentrations at cell–cell boundaries (Figure ). These results indicated that the LNCaP cells assume a disorganized, non‐polarized morphology within the spheroids, consistent with the behavior of LNCaP cells in previously investigated synthetic matrices such as functionalized hyaluronic acid …”
Section: Resultsmentioning
confidence: 97%
“…In response to the shortcomings of Matrigel, multiple synthetic 3D culture systems have received considerable interest . Synthetic matrices may avoid the most limiting aspects of Matrigel but must be designed to recapitulate the extracellular matrix's mechanical properties, transport properties, specific biological interactions, and degradation/remodeling processes that occur within the tumor microenvironment .…”
Section: Introductionmentioning
confidence: 99%
“…Organoids have been utilized as microphysiological systems to study the important morphogenetic and functional hallmarks found in the human tissues. 42,43 Recently, organoids have emerged as alternative platforms to understand cancer biology. 44,45 Hence, organoid cultures have been established for many cancer types with success rates between 15% and 100%.…”
Section: Engineering Matrices To Build Better Organoidsmentioning
confidence: 99%